ResearchMatch on FHIR: Development and evaluation of a recruitment registry and electronic health record system interface for volunteer profile completion - Alex C. Cheng; Leah Dunkel; Loretta M. Byrne; Maeve Tischbein; Delicia Burts; Jahi Hamilton; Kaysi Phillips; Bryce Embry; Jason Tan; Erik Olson; Paul A. Harris (Journal of Clinical and Translational Science, 2023)
Abstract